The roots of rap : 16 bars on the 4 pillars of hip-hop - Weatherford, Carole Boston, 1956- (Little Bee Books, 2019)
Presents the history of hip-hop including how it evolved from folktales, spirituals, and poetry, to the showmanship of James Brown, to the culture of graffiti art and breakdancing that formed around the art form.